Availability of domestic gypsum resources versus the predicted decline in synthetic gypsum production - Mazurek, Sławomir; Naworyta, Wojciech Robert (Gospodarka Surowcami Mineralnymi – Mineral Resources Management, 2026)
The ongoing decarbonization of the Polish energy sector will lead to a substantial decline in synthetic gypsum production, currently constituting 60–75% of the domestic gypsum supply. Synthetic gypsum, generated as a by-product of flue gas desulfurization (FGD) in coal- and lignite-fired power plants, is directly linked to fossil fuel combustion. Based on energy transition scenarios and projected reductions in hard coal and lignite use, synthetic gypsum production in Poland is expected to decrease from approximately 2.5–2.6 Mt in 2024 to about 1.9 Mt in 2030, 1.2 Mt in 2035, and 0.6 Mt in 2040. Assuming an annual demand of ~4 Mt and a stable natural gypsum output of ~1 Mt, a significant supply deficit is anticipated after 2025. The study evaluates documented and prospective gypsum deposits in Poland, taking into account geological conditions, resource categories, environmental constraints, and land-use restrictions. Although total geological resources are substantial, many deposits are located within Natura 2000 sites or other protected areas, limiting the feasibility of opencast mining. As an alternative, underground mining using the room-and-pillar method is proposed. This approach reduces surface disturbance and enables underground pre-processing, minimizing environmental impact. The Winiary and Siedliska deposits are identified as particularly suitable for such exploitation due to favorable geological parameters. Underground development of selected deposits may therefore constitute a strategic response to the projected shortage of synthetic gypsum in Poland.